The impact of globalization on basic education values in Indonesia - Eli Supint Zega; Laila Nurfadhila Saragih; Siti Ashila Lubis; Elfrianto Elfrianto (Holistic Science, 2025)
Globalization is a global phenomenon that brings significant changes to various aspects of life, including primary education. The increasingly open flow of information, advances in digital technology, and the intensity of cross-cultural interactions have a direct impact on educational values, character formation, and learning patterns of primary school students. This study aims to analyze the impact of globalization on the values of primary education in Indonesia, both positively and negatively. The method used is a literature study with a qualitative approach, through a review of various relevant scientific sources, such as journal articles, books, and research reports. The results of the study indicate that globalization has a positive contribution in expanding access to information, improving the quality of learning, and developing 21st-century competencies. However, globalization also has the potential to erode character values, morals, and local cultural wisdom if not balanced with the strengthening of values-based education. Therefore, an adaptive primary education strategy is needed that places character education and Pancasila values as the main foundation in facing the challenges of globalization.